A Tropical Cocktail of Organic Matter Sources: Variability in Supraglacial and Glacier Outflow Dissolved Organic Matter Composition and Age Across the Ecuadorian Andes - Holt, Amy D.; Kellerman, Anne M.; Battin, Tom. I.; McKenna, Amy M.; Hood, Eran; Andino, Patricio; Crespo-Pérez, Verónica; Peter, Hannes; Schön, Martina; De Staercke, Vincent; Styllas, Michail; Tolosano, Matteo; et al. (Journal of Geophysical Research: Biogeosciences, 2023)
The biogeochemistry of rapidly retreating Andean glaciers is poorly understood, and Ecuadorian glacier dissolved organic matter (DOM) composition is unknown. This study examined molecular composition and carbon isotopes of DOM from supraglacial and outflow streams (n = 5 and 14, respectively) across five ice capped volcanoes in Ecuador. Compositional metrics were paired with streamwater isotope analyses (δ18O) to assess if outflow DOM composition was associated with regional precipitation gradients and thus an atmospheric origin of glacier DOM. Ecuadorian glacier outflows exported ancient, biolabile dissolved organic carbon (DOC), and DOM contained a high relative abundance (RA) of aliphatic and peptide-like compounds (≥27%RA). Outflows were consistently more depleted in Δ14C-DOC (i.e., older) compared to supraglacial streams (mean −195.2 and −61.3‰ respectively), perhaps due to integration of spatially heterogenous and variably aged DOM pools across the supraglacial environment, or incorporation of aged subglacial OM as runoff was routed to the outflow. Across Ecuador, Δ14C-DOC enrichment was associated with decreased aromaticity of DOM, due to increased contributions of organic matter (OM) from microbial processes or atmospheric deposition of recently fixed and subsequently degraded OM (e.g., biomass burning byproducts). There was a regional gradient between glacier outflow DOM composition and streamwater δ18O, suggesting covariation between regional precipitation gradients and the DOM exported from glacier outflows. Ultimately, this highlights that atmospheric deposition may exert a control on glacier outflow DOM composition, suggesting regional air circulation patterns and precipitation sources in part determine the origins and quality of OM exported from glacier environments.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007188
Keywords: cryosphere; dissolved organic carbon; Dissolved organic matter; Ecuador; FT-ICR MS; glaciers; δ13C-DOC; Δ14C-DOC

Limited Presence of Permafrost Dissolved Organic Matter in the Kolyma River, Siberia Revealed by Ramped Oxidation - Rogers, Jennifer A.; Galy, Valier; Kellerman, Anne M.; Chanton, Jeffrey P.; Zimov, Nikita; Spencer, Robert G. M. (Journal of Geophysical Research: Biogeosciences, 2021)

Unifying Concepts Linking Dissolved Organic Matter Composition to Persistence in Aquatic EcosystemsUnifying Concepts Linking Dissolved Organic Matter Composition to Persistence in Aquatic Ecosystems - Kellerman, Anne M.; Guillemette, François; Podgorski, David C.; Aiken, George R.; Butler, Kenna D.; Spencer, Robert G. M. (Environmental Science & Technology, 2018)
The link between composition and reactivity of dissolved organic matter (DOM) is central to understanding the role aquatic systems play in the global carbon cycle; yet, unifying concepts driving molecular composition have yet to be established. We characterized 37 DOM isolates from diverse aquatic ecosystems, including their stable and radiocarbon isotopes (δ13C-dissolved organic carbon (DOC) and Δ14C-DOC), optical properties (absorbance and fluorescence), and molecular composition (ultrahigh resolution mass spectrometry). Isolates encompassed end-members of allochthonous and autochthonous DOM from sites across the United States, the Pacific Ocean, and Antarctic lakes. Modern Δ14C-DOC and optical properties reflecting increased aromaticity, such as carbon specific UV absorbance at 254 nm (SUVA254), were directly related to polyphenolic and polycyclic aromatic compounds, whereas enriched δ13C-DOC and optical properties reflecting autochthonous end-members were positively correlated to more aliphatic compounds. Furthermore, the two sets of autochthonous end-members (Pacific Ocean and Antarctic lakes) exhibited distinct molecular composition due to differences in extent of degradation. Across all sites and end-members studied, we find a consistent shift in composition with aging, highlighting the persistence of certain biomolecules concurrent with degradation time.